Methicillin-Resistant Staphylococcus aureus Endocarditis and de Novo Development of Daptomycin Resistance during Therapy. Issue 2 (2010) - Twele, L; Moyen, E; Zhang, K; Dalton, B; Church, D; Conly, J
Abstract : Daptomycin resistance in Staphylococcus aureus has been previously reported, but the development of resistance while on therapy with subsequent clinical failure for endocarditis has been infrequently reported. A case of persistent methicillin-resistant S aureus (MRSA) bacteremia in the setting of right-sided endocarditis in a 38-year-old man with a history of intravenous drug use is presented. He developed de novo resistance to daptomycin during therapy after several courses of antibiotics, with subsequent clinical failure. Isolates were identified by molecular characterization to be community-acquired MRSA 10 (USA300). To the authors' knowledge, the present case was the first in Canada to involve the de novo development of daptomycin resistance with clinical failure due to MRSA during therapy for endocarditis. Clinicians and microbiologists must be aware of this phenomenon given the implications for treatment and transmission of the strain. It also raises questions regarding the use of daptomycin in settings of heavily pretreated patients with persistent MRSA bacteremia.